2019
DOI: 10.1111/1462-2920.14831
|View full text |Cite
|
Sign up to set email alerts
|

Identification of flavonoids as regulators of YbeY activity in Liberibacter asiaticus

Abstract: Summary Liberibacter asiaticus is the prevalent causative pathogen of Huanglongbing or citrus greening disease, which has resulted in a devastating crisis in the citrus industry. A thorough understanding of this pathogen's physiology and mechanisms to control cell survival is critical in the identification of therapeutic targets. YbeY is a highly conserved bacterial RNase that has been implicated in multiple roles. In this study, we evaluated the biochemical characteristics of the L. asiaticus YbeY (CLIBASIA_0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Moreover, substitution H128A, which lowers the RNase activity of the recombinant human enzyme, does not affect its ability to complement a YBEY KO, similar to the equivalent substitution in E. coli ( 8 ). Likewise, substitution R55A, which severely impairs the RNase activity of bacterial YbeY ( 5 , 12 ), fully complements YBEY deletion in humans and B. subtilis ( 3 ) and restores 16S rRNA processing in E. coli ( 8 ), B. subtilis ( 3 ) and Liberibacter asiaticus ( 19 ). These observations suggest that the apparent RNase activity of YBEY is not necessarily related to ribosome biogenesis, calling for further studies to clarify its nature and significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, substitution H128A, which lowers the RNase activity of the recombinant human enzyme, does not affect its ability to complement a YBEY KO, similar to the equivalent substitution in E. coli ( 8 ). Likewise, substitution R55A, which severely impairs the RNase activity of bacterial YbeY ( 5 , 12 ), fully complements YBEY deletion in humans and B. subtilis ( 3 ) and restores 16S rRNA processing in E. coli ( 8 ), B. subtilis ( 3 ) and Liberibacter asiaticus ( 19 ). These observations suggest that the apparent RNase activity of YBEY is not necessarily related to ribosome biogenesis, calling for further studies to clarify its nature and significance.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, YbeY has been described as a metal-dependent endoribonuclease ( 5 , 12 , 18 ), and in some bacteria, ybeY mutants accumulate 16S rRNA with an unprocessed 3′ end ( 3 , 5 , 7 , 8 , 18 , 19 ). Therefore, YbeY was proposed to be the ‘missing’ 3′ endoribonuclease required for 16S rRNA maturation to obtain the correct anti-Shine-Dalgarno sequence, which is needed for translation initiation on most bacterial mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the YbeY portion of the bacterium's genetic code was found to play an important role in bacterial symbiosis and pathogenicity. 38 Tested flavones and flavonols showed a significant reduction in CLas titer in HLBinfected citrus trees. 38 On the other hand, the flavanones (hesperetin and naringenin) were found to have little to no inhibitory effect.…”
Section: Discussionmentioning
confidence: 93%
“…9 Flavonoids, which are also considered as a group of phenolic compounds, have a good antioxidant activity. 26,37 Recently, Zuo et al (2019) showed that flavones such as luteolin and apigenin and flavonols (quercetin) had potent inhibitory effects on YbeY of CLas bacterium. 38 YbeY is considered part of the 206 genes that make up the minimal bacterial genome set, which is necessary for the maturation of RNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation